(untitled) (mathematica didactica, 2014)
This paper reports on a pretest-posttest study regarding the trainability of mathematical problem solving focusing on five different heuristic strategies (a replication with improved circumstances) and two different kinds of instruction (explicit and implicit). 28 student teachers were separated into three groups: an experimental group (problem-solving and heuristic training), a control group (only problem-solving training) and a comparison group (no training). The study shows a significant advantage of the combined training.